Improving growth and yield of rice through the use of agricultural Jiaosu in different combinations - Rui Zhang; Chao Zhang; Xiangyu Xiong; Guohua Zhou; Yanyun Yi; Sisi Hong; Jifang Li; Qinghai Song; Fei Ye; Ying Liu; Wenjun Zhou (Circular Agricultural Systems)
Agricultural Jiaosu is rich in nutrients and plant-beneficial microbial communities, and thus has great potential in reducing fertilizer dosage and improving fertilizer use efficiency. This pot experiment was conducted to investigate the effects of agricultural Jiaosu on the growth and yield of rice. The experiment employed three agricultural Jiaosu treatments (i.e., soil solid agricultural Jiaosu, soil liquid agricultural Jiaosu, leaf liquid agricultural Jiaosu) in various combinations, along with one control treatment (chemical fertilizer). Results revealed that plant height of rive agricultural Jiaosu treatments were higher than that of the control treatment, with the ranks as follows: JT (soil solid agricultural Jiaosu + soil liquid agricultural Jiaosu), JY (soil solid agricultural Jiaosu + leaf liquid agricultural Jiaosu), JA (soil solid agricultural Jiaosu + soil liquid agricultural Jiaosu + leaf liquid agricultural Jiaosu) and F (conventional fertilizer) during harvest. The ratio of panicle biomass to total biomass and straw of three types of Jiaosu treatments was significantly higher than that in the chemical fertilizer treatment, indicating that agricultural Jiaosu treatment altered the dry matter distribution characteristics of rice. The yield per plant of JA treatment (49.35 ± 2.43 g) was 8.51% higher than chemical fertilizer treatment. Additionally, the correlation between soil nutrients and plant growth and yield analysis indicated that agricultural Jiaosu has higher nutrient use efficiency with lower input of N, P, and K. The study highlights the potential function of agricultural Jiaosu in promoting crop growth and yields while reducing the need for fertilization.